Artificial intelligence innovations in genetic technology: DNA-based diagnostics for the future of medicine - Thandar Htwe; Aung Myint; Muntasir Muntasir (Journal of World Future Medicine, Health and Nursing, 2025)
Advancements in artificial intelligence (AI) are revolutionizing the field of genetic technology, particularly in DNA-based diagnostics, offering promising applications for the future of medicine. The rapid growth of AI in the analysis of genetic data allows for faster, more accurate, and cost-effective diagnostic processes. This study explores the integration of AI innovations in DNA diagnostics and their potential to transform clinical practices. Using a systematic review methodology, this research evaluates the current AI-driven genetic diagnostic technologies, focusing on their impact on disease detection, genetic mutation identification, and personalized treatment strategies. The findings reveal that AI-based tools, such as deep learning and machine learning algorithms, significantly improve the accuracy and speed of genetic diagnoses, particularly in rare genetic disorders and cancers. These technologies are also shown to enhance the predictive power of genetic tests, offering insights into patients' future health risks. The study concludes that AI-driven DNA diagnostics hold the potential to revolutionize medical practice, providing more precise, individualized care while reducing healthcare costs. However, challenges related to data privacy, algorithm transparency, and the need for large-scale clinical validation remain.